Anatomic variation of the superficial peroneal nerve in the operative field during direct lateral approach for distal fibula fracture - Seungyup Shin; Seong-Tae Kim; Gyeonggyu Choi; Sungho Lee (Trauma Case Reports)
The superficial peroneal nerve (SPN) is frequently at risk of iatrogenic injury during the open reduction and internal fixation of the distal fibula. The risk of nerve injury is increased for the Blair and Botte type B pattern of SPN, crossing the distal fibula from posterior to anterior (at 5 to 7 cm) from the lateral malleolar tip. Recently, two cases of Blair and Botte type B pattern were observed during the open reduction and internal fixation of the distal fibula at our hospital. Herein, the authors describe two cases of anatomic variation of SPN with a literature review.